Materiały SrB4O7 i BaTiO3 aktywowane lantanowcami (III lub II) do luminescencyjnej manometrii i nieliniowej, optycznej termometrii - Zheng, Teng (My University, 2022)
Rozprawa doktorska poświęcona jest badaniom właściwości strukturalnych i fotoluminescencyjnych (PL) wybranych nieorganicznych matryc, tj. SrB4O7 i BaTiO3, domieszkowanych jonami Ln2+ lub Ln3+. Głównym celem pracy było opracowanie i scharakteryzowanie manometrów i termometrów optycznych. Do stabilizacji Ln2+ wybrano kilka matryc boranowych, tj. SrB4O7, SrB2O4 i Sr3(BO3)2. Zbadany został wpływ matrycy na właściwości strukturalne, morfologiczne i PL materiałów. Zaproponowano kilka strategii optycznego wykrywania ciśnienia: I) strategię wzmocnienia sygnału luminescencyjnego (~60 razy) pasma Sm2+: 5D0→7F0 poprzez proces transferu energii Eu2+→Sm2+ w domieszkowanym czujniku SrB4O7; II) Strategia wykorzystania wzmocnionej ciśnieniowo (wzmocnienie o 3 rzędy wielkości) emisji 4f-4f Eu2+ w SrB4O7 do optycznego wykrywania ciśnienia w zakresie wysokiego ciśnienia (~60 GPa). III) Emisja 5d-4f jonów Tm2+ w tej samej matrycy została zastosowana jako czujnik obu parametrów (p i T). Jednoczesne generowanie drugiej harmonicznej (SHG) i luminescencji upkonwersyjnej (UCL) zaobserwowane zostało w dobrze znanej matrycy BaTiO3 domieszkowanej Ln3+. W ten sposób opracowano nowatorską strategię – nieliniową, optyczną termometrię opartą na wrażliwych na symetrię procesach SHG i termoczułych procesach UCL w znanej matrycy BaTiO3 domieszkowanej jonami Ho3+ i Yb3+. Ponadto analiza PL i termometryczna w układzie BaTiO3 domieszkowanym Er3+ i Yb3+ pozwoliła na szczegółowe porównanie konwencjonalnej termometrii Boltzmanna (opartej na TCLs Er3+) z nieliniową termometrią optyczną.

The doctoral dissertation is devoted to the investigation of the structural and PL performances of selected inorganic host matrices, i.e., SrB4O7 and BaTiO3, doped with Ln2+ or Ln3+. The main goal of the work was to develop and characterize optical manometer and thermometer. Several borate matrices, i.e., SrB4O7, SrB2O4 and Sr3(BO3)2, were selected for stabilization of Ln2+. The influence of the matrix on the structural, morphological and PL properties has been systematically investigated and analysed. Subsequently, several strategies of optical pressure sensing were proposed: I) the strategy of luminescent signal enhancement (~ 60 times) of Sm2+: 5D0→ 7F0 peak through the Eu2+→Sm2+ ET process in the co-doped SrB4O7 pressure sensor; II) The strategy to use the pressure-enhanced (enhancement by 3 orders magnitude) 4f-4f emission of Eu2+ in SrB4O7 for the optical pressure detection towards the higher-pressure range (~60 GPa). III) For the first time, the 5d-4f emission of Tm2+ in the same matrix has been applied as a bifunctional platform. On the other hand, second harmonic generation (SHG) and up-conversion luminescence (UCL) were observed simultaneously in the well-established BaTiO3 matrix doped with Ln3+. Thus, novel strategy was developed – non-linear optical thermometry based on symmetry-sensitive SHG and thermal-sensitive UCL processes in the well-established BaTiO3 matrix doped with Ho3+-Yb3+. Moreover, the PL and thermometric analysis in the Er3+-Yb3+ co-doped BaTiO3 system allows for a detailed comparison of conventional Boltzmann thermometry (based on TCLs of Er3+) and non-linear optical thermometry.
Lanthanide (III or II) activated SrB4O7 and BaTiO3 materials for luminescent manometry and non-linear optical thermometry
Keywords: SrB4O7; BaTiO3; czujnik ciśnienia; nieliniowa optyczna termometria; lantanowce; lanthanides; pressure sensing; non-linear optical thermometry